Physical Test of Avocado Leaf Extract Cream Formula - Yulianto, Susilo; Wulandari, Septefine (CV. Ulil Albab Corp, 2024)
Avocado (Perseaamericana Mill) is a plant that grows widely in subtropical and tropical areas, one of which is Indonesia. The leaves of the avocado plant, which we can use as traditional medicine, are reported to be anti-bacterial and can inhibit the growth of several bacteria, including Staphylococcus aurus. The active substances contained in avocado leaves are flavonoids, quercetin and tannin which are useful as anti-bacterials and as a source of natural antioxidants. This study aims to determine the results of the physical test of the avocado leaf extract cream formula. This type of research is quantitative with a descriptive research design. In testing the cream, an organoleptic test, homogeneity test, pH test, spreadability test, absorption test and adhesion test were carried out. The results obtained in the organoleptic test were seen from the yellowish brown color, the semi-solid dosage form, and the distinctive creamy smell of avocado leaves, the homogeneity test of the cream did not occur in phase separation, namely the water phase and the oil phase, the pH test of the cream had a pH of 7, the power test Spread the cream with a diameter of 6.1 cm, the cream's absorption test can absorb water optimally, and the cream's adhesion test obtains an adhesion time of 1.48 seconds. The physical test of the avocado leaf extract cream formula meets the requirements.